2013
DOI: 10.1055/s-0033-1351074
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: Therapeutical Potential in Ophthalmology

Abstract: Curcumin (diferuloylmethane) is the main curcuminoid of the popular Indian spice turmeric (Curcuma longa). In the last 50 years, in vitro and in vivo experiments supported the main role of polyphenols and curcumin for the prevention and treatment of many different inflammatory diseases and tumors. The anti-inflammatory, antioxidant, and antitumor properties of curcumin are due to different cellular mechanisms: this compound, in fact, produces different responses in different cell types. Unfortunately, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 53 publications
0
80
0
3
Order By: Relevance
“…Natural products may serve as nutraceutical therapeutic interventions and as lead compounds for the specific, efficacious, and affordable drugs with minimal side effects in the eye and its related disorders [25]. Evidence suggests that curcumin and resveratrol may have potential in the treatment of several ocular diseases [39,40]. Scutellarin inhibits retinal angiogenesis through disturbing ROS/HIF-1α/VEGF pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products may serve as nutraceutical therapeutic interventions and as lead compounds for the specific, efficacious, and affordable drugs with minimal side effects in the eye and its related disorders [25]. Evidence suggests that curcumin and resveratrol may have potential in the treatment of several ocular diseases [39,40]. Scutellarin inhibits retinal angiogenesis through disturbing ROS/HIF-1α/VEGF pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]33,34,39 In this study, we partially elucidated the molecular mechanisms of cell apoptosis in diabetes-induced rats and demonstrated that curcumin was excellent for treatment. We found that neuronal loss occurred in the retinas of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have not yet been able to elucidate the mechanisms by which curcumin prevents the progression of diabetic retinopathy. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Although many studies have reported that curcumin rescues retinal neuronal cell cultures from glutamate toxicity, 36,37 researchers have not been able to determine how curcumin treatment ameliorates the diabetes-induced damage to retinal Department of Ophthalmology, Lishui Central Hospital and Fifth Affiliated Hospital of Wenzhou Medical University, Lishui, Zhejiang Province, People's Republic of China. *These two authors contributed equally to the work and therefore should be considered equivalent authors.…”
mentioning
confidence: 99%
“…[71819] The curcumin is a natural polyphenolic compound of low toxicity and is considered the main compound of the rhizome. [202122] Thanks to its different pharmacological actions, curcumin and its analogs have been employed in different studies involving several pathologies such as cardiovascular and ophthalmic diseases, diabetes, depression, HIV, vitiligo, Alzheimer’s disease, endometriosis, osteoporosis, inflammatory bowel disease, epilepsy, Parkinson’s disease, and cancer [Figure 1]. [8910212324252627282930]…”
Section: Curcuma Longamentioning
confidence: 99%